THEORETICAL PROBLEMS OF RESEARCHING THE DUTIES OF THE STATE - Матвійчук, Анатолій Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article examines the duties of the state as a legal category. The views of scientists on understanding the problems of the legal category and the duties of the state as a legal category are analyzed. Methods of research: on the basis of a theoretical understanding of the concept of «legal category», the notion of «state obligations as a legal category» is formulated. The results: are supplemented by a concept-categorical apparatus with a new concept. It is concluded that the duties of the state as a legal category is the established and guaranteed necessity of the state actions (and / or abstention from them), which is carried out by the bearers of its duties in the manner and within the limits determined by the Constitution and laws of the state. The components of the state’s responsibilities as a legal category are defined.